2021
DOI: 10.1177/07311214211012018
|View full text |Cite
|
Sign up to set email alerts
|

Working Differently or Not at All: COVID-19’s Effects on Employment among People with Disabilities and Chronic Health Conditions

Abstract: The COVID-19 pandemic has drastically changed employment situations for workers everywhere. This is especially true among people with disabilities and chronic health conditions who face greater risks in contracting COVID-19 and experience larger disadvantages within the labor market. Drawing from original data gathered through a national online survey ( N = 1,027) and integrated set of virtual interviews ( N = 50) with Canadians with disabilities and chronic health conditions, our findings show that although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 62 publications
2
28
0
Order By: Relevance
“…One plausible reason for this disparity between those with and without CID could be that people with CID are more likely to work as temporary or on-call staff who tend to be the first group of employees to be laid-off or furloughed during budgetary constraint situations (Maroto & Pettinicchio, 2020). Indeed, these findings substantiate concerns expressed by part-time and nonunion workers with CID in Canada who expressed fears of losing their jobs during the pandemic (Maroto et al, 2021). Another plausible reason for the disparity could be that the type of work that people with CID do is more likely to require physical presence at the workplace or to be considered an “essential job.” It is concerning that individuals with CID were more likely to lose their jobs and/or not able to work from home, as this is already a vulnerable group that may be more susceptible to physical and psychological health problems (Beatty, 2012; Detaille et al, 2009), socioeconomic challenges (Jalali et al, 2020), and societal isolation (Armitage & Nellums, 2020) that could be exacerbated by such employment situations.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…One plausible reason for this disparity between those with and without CID could be that people with CID are more likely to work as temporary or on-call staff who tend to be the first group of employees to be laid-off or furloughed during budgetary constraint situations (Maroto & Pettinicchio, 2020). Indeed, these findings substantiate concerns expressed by part-time and nonunion workers with CID in Canada who expressed fears of losing their jobs during the pandemic (Maroto et al, 2021). Another plausible reason for the disparity could be that the type of work that people with CID do is more likely to require physical presence at the workplace or to be considered an “essential job.” It is concerning that individuals with CID were more likely to lose their jobs and/or not able to work from home, as this is already a vulnerable group that may be more susceptible to physical and psychological health problems (Beatty, 2012; Detaille et al, 2009), socioeconomic challenges (Jalali et al, 2020), and societal isolation (Armitage & Nellums, 2020) that could be exacerbated by such employment situations.…”
Section: Discussionsupporting
confidence: 70%
“…One plausible reason for this disparity between those with and without CID could be that people with CID are more likely to work as temporary or on-call staff who tend to be the first group of employees to be laid-off or furloughed during budgetary constraint situations (Maroto & Pettinicchio, 2020). Indeed, these findings substantiate concerns expressed by part-time and nonunion workers with CID in Canada who expressed fears of losing their jobs during the pandemic (Maroto et al, 2021). Another plausible reason for the disparity could be that the type of work that people with CID do is more likely to require physical presence at the workplace or to be considered an "essential job."…”
Section: Covid-19 Impacts On Employmentsupporting
confidence: 58%
“…There is evidence that people with disabilities have been particularly affected by these challenges. For example, research suggests that pandemic mitigation efforts have been most burdensome to people with disabilities in terms of employment costs – in losses of employment, reduced employment, lower wages, and the inability to seek new employment opportunities ( Ciciurkaite et al, 2021 ; Kuper et al, 2020 ; Maroto et al, 2021 ). As an illustration, an analysis of data from the Current Population Survey observed that the employment rate of people with disabilities dropped 24% in the first two months of the pandemic in the U.S. – March and April – alone ( Maroto et al., 2021 ).…”
Section: Applications To the Pandemic Contextmentioning
confidence: 99%
“…The pandemic has also highlighted pre-existing employment inequalities and fueled the biases that serve to reinforce them ( Ciciurkaite et al, 2021 ; Maroto et al, 2021 ), which is further detrimental to the psychological well-being of socially-marginalized groups. People with disabilities, for example, have long experienced ableism, which is defined as prejudice, discrimination, and the application of stigma toward people with disabilities ( Friedman & Owen, 2017 ).…”
mentioning
confidence: 99%
“…Michelle Lee Maroto, David Pettinicchio, and Martin Lukk (2021) focus on the experience of workers with disabilities and chronic conditions in Canada. This is a category of workers who experience greater disadvantages in standard times and who have significant health risks in the context of COVID-19.…”
Section: Contributions To the Special Issuementioning
confidence: 99%